Pengembangan Program Pembelajaran Internet of Things Control Solution (IoT Consol) pada Mata Kuliah Media Pembelajaran Fisika - Nurlia, Siti Rosyadah; Guntara, Yudi; Saefullah, Asep (Universitas Sultan Ageng Tirtayasa, 2024)
This research focuses on developing an Internet of Things control solution (IoT consol) learning program in physics learning media courses. This study uses the Research and Development (R&D) method with the Thiagarajan 4D development model consisting of four stages: Define, Design, Develop, and Disseminate. The learning program products include semester learning plans, student worksheets, learning modules, and assessment sheets. Data collection techniques include product feasibility test sheets and student response questionnaire sheets. The feasibility test data for the learning program is analysed descriptively based on the feasibility test criteria for product development, referring to the Likert scale 1-7. The results of the product development research obtained a feasibility value with overall feasibility criteria for learning device elements with a value of 93% in the very good category, and the results of student responses obtained a value of 77.77% in the good category. The developed IoT consol learning program was feasible for physics learning media courses based on data analysis.